Unsteady three-dimensional MHD nanofluid flow over a stretching sheet with variable wall thickness and slip effects - Kumar, Gunda Vinod; Varma, Vijayakumar S.; Kumar, R.V.M.S.S.K. (Zielona Góra: Uniwersytet Zielonogórski)
The stretching sheets with variable thickness may occur in engineering applications more frequently than a flat sheet. Due to its various applications, in the present analysis we considered a three dimensional unsteady MHD nanofluid flow over a stretching sheet with a variable wall thickness in a porous medium. The effects of radiation, viscous dissipation and slip boundary conditions are considered. Buongiorno`s model is incorporated to study the combined effects of thermophoresis and Brownian motion.
Keywords: unsteady flow; magnetic field; Buongiorno`s model; variable wall thickness sheet; velocity; thermal slip; solutal slip